Community of Latin American and Caribbean States (CELAC): procedures for the organic functioning of CELAC - Estados Latinoamericanos y Caribeños, Comunidad de (2012)
The operating organs and procedures of CELAC are established: 1.- Summit of Heads and Heads of State and Government; 2.- Meeting of Ministers of Foreign Affairs; 3.- Pro Tempore Presidency; 4.- Meeting of National Coordinators; 5.- Specialized meetings; 6.- Troika.